GAMBARAN KECEMASAN ATLET BOLA VOLI KLUB CITRA BAKTI DITINJAU DARI JENIS KELAMIN - Yanuarius Ricardus Natal; Yunita Victoria Natal (Jurnal Pendidikan Olah Raga, 2023)
Volleyball is a type of competitive sport that is quite popular among Indonesian people who demand quality from their athletes. The aim of this research is to look at the picture of anxiety in volleyball athletes at the Citra Bakti club in terms of gender. The population in this study was 24 athletes with the sampling technique used in this research using a saturated sampling technique, that is, the entire population was used in this study and 12 male athletes were obtained and 12 female athletes were obtained. The research instrument used was adapted from question items in the Halmilton Anxiety Rating Scale (HARS) which had been modified by researchers with anxiety responses, namely physiological, cognitive, behavioral and affective responses. The data analysis technique used uses an independent sample t-test to determine whether or not there is a difference in the average between the two sample groups. The results of data analysis regarding anxiety variables for male athletes and female athletes using the independent sample t-test showed that the T value for male athletes resulting from anxiety was 0.450 with a significance level of 0.658. The T table value with a significance level of 5% is 1.717. Because the calculated T value < T table (0.450 < 1.717 and the significance value is 0.658 > 0.0, it can be concluded that there is no difference in anxiety between male and female athletes.